Kolomna Machine-Building Plant during the Great Patriotic War: Defense and Civil Production - Mikhail Yu. Sergomasov; Evgeny L. Lomako (RUDN Journal of Russian History, 2025)
The authors examine the activities of the Kolomna Machine-Building Plant during the harsh years of the Great Patriotic War. The authors show the process of rapid restructuring of the enterprise for defense production, including the production of armored hulls for the T-60 tank, platform wagons for 25 mm and 37 mm anti-aircraft guns, Katyusha rocket launchers, artillery shells, and armored trains. The study also reveals the features of the evacuation of tank production to Kirov and the production facilities involved in the manufacturing of platform wagons for anti-aircraft guns for Krasnoyarsk in October 1941. The authors analyze the activities of the specialists, who after the evacuation of the main production facilities, remained near the frontline Kolomna to organize complete overhaul of tanks and self-propelled artillery guns damaged on the battlefield and to produce crowfeet and cast steel turret of machine-gun position for the construction of a fortified area on the probable way of the Fascist offensive on Moscow. These workers also produced metallurgical and mining equipment during the same period. The material of the article is based on: the decisions and resolutions of the State Defense Committee, archival documents from the museum of the joint stock company “Kolomensky Zavod,” the company managers’ memoirs, and other historical research. It was found that in the most difficult conditions of wartime, the specialists and equipment of the Kolomna Machine-Building Plant had become the basis for the creation of large defense enterprises in Siberia and after the liberation of Donbass - in Kharkov. The specialists who remained in Kolomna, along with some of those evacuated from Kirov and the besieged Leningrad, also managed to recover the design and production of mainline steam locomotives and medium-speed piston engines at the Kolomna Machine-Building Plant.